Factors Influencing User Satisfaction and Operational Efficiency of the Prince of Songkla University Management Accounting System (PSU MAS): Perspectives from Financial and Accounting Officers at Prince of Songkla University - Tearapattragul, Anna (Journal of Information and Learning [JIL], 2025)
This study aims to examine the factors influencing user satisfaction and operational efficiency of the PSU MAS from the perspectives of financial and accounting officers at Prince of Songkla University. A quantitative approach using survey research was employed. The sample consisted of 142 financial and accounting officers from five campuses. The research instrument was a questionnaire validated by experts (IOC = 0.86) and demonstrated high reliability (Cronbach’s alpha = 0.91). Data were analyzed using Exploratory Factor Analysis (EFA) and Multiple Regression Analysis. The findings revealed three key factors affecting system performance: decision support capability, data accuracy, and operational error checking. Among these, decision support capability had the most significant influence on system efficiency. These findings were interpreted through the U-DO framework, which emphasizes user-centered evaluation, decision support functionality, and operational error management, highlighting the practical needs of end users in the university context. Based on the results, strategic and operational recommendations were developed under the GROW–WISE framework. The GROW component offers university-level strategic guidance, including inclusive governance, system integration, centralized financial platforms, and long-term investments. The WISE component focuses on operational-level improvements, such as user-friendly interface design, intelligent reporting, real-time error checking, and continuous user feedback. These insights have practical implications for enhancing PSU MAS to better align with real-world usage and strengthen its role as a strategic decision-making tool for higher education institutions in Thailand.